Стратегия модернизации и политика доходов: концептуальный анализ (Путеводитель предпринимателя, 2020)
This scientific article reveals some of the basic foundational statements of investigating concepts of social goals, those are the primary tasks of Russian gouvernement policy and scientifically formulating of contemporary challenges of modern viewing of«market economy». The author also points out the necessity of investments into not only production tools, but in diversement and reforms takings in human educational and labor changes to obtain new development stages social-economic advantages.